Sentinel Lymph Node Biopsy in Early Breast Cancer: The Experience of the European Institute of Oncology in Special Clinical Scenarios - Toesca, Antonio (S. Karger GmbH, 2011)
BACKGROUND: While axillary nodal status is still one of the most important prognostic factors in breast cancer, sentinel lymph node biopsy (SLNB) has evolved as a main procedure to strongly reduce postsurgical morbidity improving early and long-term quality of life. MATERIAL AND METHODS: Between 1996 and 2010, we performed 18,884 SLNBs for breast cancer, successfully confirming the validity of this technique and its positive impact on patients' quality of life, even though decision-making processes for adjuvant treatment strongly depend on biological features. RESULTS: This paper summarizes published data mainly collected in our institute considering special clinical scenarios such as ductal intraepithelial neoplasia, intramammary sentinel nodes, multicentric breast cancer, prior breast surgery, previous breast aesthetic surgery, second axillary SLNB, pregnant patients, primary chemotherapy, and male patients. CONCLUSIONS: In general, we believe that SLNB represents the standard procedure for axillary staging in virtually all clinical situations, even in those which were previously considered a contraindication for this procedure. At the moment, the only contraindication to SLNB is the presence of documented axillary metastases.